Does Financial Performance Of Local Government Influence On The Audit Agency Opinion? - Khairudin KHAIRUDIN (Jurnal Akuntansi dan Keuangan, 2013)
Based on information from BPK RI (2013) that LKPD opinion from 2007 until 2011 has a positive development and achievements of local governments in financial management. From year to year where local governments obtain an unqualified opinion (WTP) for the financial statements continue to grow, although the progress is not as expected. The objectives of this research is to compare the financial performance of the District Government /Cities in Indonesia which concurs with WTP and non-WTP opinion from BPK. Therefore, the problems in this study is whether the financial performance of the District Government / Cities in Indonesia who opined WTP better and significantly different from the non-WTP. Using cluster sampling, this study selectt 122 local government in Indonesia, which consists of 57 District who opined WTP, and 65 District opined that non-PAP. Meanwhile, the local governments financial performance measure used in this study is the ratio of the area of financial independence, effectiveness ratio, efficiency ratio, and growth ratios. From statistical test results, this study conclude that the financial performance of the District Government /Cities in Indonesia who opined WTP is significantly different and better than the non_WTP for fiscal year 2011 data. These findings imply that in line with what was predicted earlier that the local government has WTP keunangan should also have a better performance compared well with the local governments do not.